The Torah revealed : - Finkel, Avraham Yaakov (Jossey-Bass, 2004)
n The Torah Revealed, distinguished Rabbi Avraham Yaakov Finkel brings together in one comprehensive and accessible resource expert commentary from the Talmud on key passages contained in every portion of the Torah. This important book provides an inspiring commentary on the Five Books of Moses culled from a huge body of work that represents the thoughts of the greatest Talmudic authorities of all time. This book offers an invaluable guide for rabbis preparing their weekly sermons, individuals wanting to understand the deeper meaning of the “parsha,” and students of the Torah and Talmud needing an expert analysis and explanation of the written text. The Torah Revealed helps readers to understand the significance of the Torah’s passages illuminating explicit stories, underlying allegories, metaphors, and symbolic meanings. It highlights the lessons that can be learned and applied to our own daily lives and the different ways the passages can be interpreted